صورة المرأة الإماراتية في الدراما التلفزيونية الإماراتية دراسة تحليلية ميدانية - ناجيه البادي جميل على الكتبي
The study aimed to describe and analyze the image of Emirati women in Emirati series broadcasted on Abu Dhabi and Dubai channels during the five-year period of 2016-2020. The study employed the descriptive analytical approach, using the content analysis method for a sample of 450 episodes from 15 Emirati series. A set of questionnaires was also distributed to a random sample of 430 female students from the United Arab Emirates University. In addition, interviews were also conducted on a group of Emirati writers, actors, directors, and producers. The study reached several results, the most important of which are: 46% of the study sample series dealt with the period before the discovery of oil, so it did not reflect the image of Emirati women as it is in the current reality in terms of educational, professional, and economic levels, with the illiteracy rate reaching 77% and the rate of housewives touching 63%. The study found that soap operas presented women in a stereotypical fashion, where the romantic image of women showed the highest percentage of 24%, the percentage of female actresses in soap operas in the study sample was 30%, compared to 70% for male actors, and the negative values reflected by women in soap operas reached 62%. Among the contributions of the study include submitting a proposal to establish the Emirates Drama Academy. The study recommended the necessity of establishing a national fund to support Emirati drama, dedicating an academic subject on the image of women in the media to university students, adopting art criticism of dramatic works, and paying attention to public survey studies in order to know the audience's sense of tastes.